Partnerstwo publiczno-prywatne : korzyści i zagrożenia - Braziewicz, Olga (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2005)
Public-private partnership is quite a new term in Polish economy: there is little experience enabling the empirical identification of the profits of using this model. The vast majority of Polish knowledge is based on foreign practice and trials of its theoretical adjustment to our conditions. This basis shows a clear perspective that the role of PPP is meant to grow. The knowledge of mechanisms of partnership and its specification should allow to maximize the profits which can be obtained by realization of a particular project in such a way. What is more, it will enable the introduction of some huge, capital-absorbing infrastructural investments which are needed in Poland. The list of potential advantages is much longer than the list of disadvantages. However, the application of PPP should be treated with some caution, it should be considered as one of many possible solutions. It is necessary to carry out previous analysis and PPP should be used only if its profits for the public interest outweigh other means of realization of a project. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1083, s. 640-647